A Journey of Two Countries: A Comparative Study of the Death Penalty in Israel and South Africa - Sharoni, Michelle M. (2001)
The death penalty remains a complex and controversial topic in many countries all around the world. Israel and South Africa have traveled along diverse and fascinating paths in deciding whether the death penalty is constitutional. This Note examines the history of the death penalty in Israel and South Africa, emphasizing the process of its abolition. This Note reviews the sources of Hebrew law, the history of the death penalty in Israel and the Jewish legal system. It addresses the history of the death penalty in South Africa, from the period of the early settlers up to a recent unanimous decision to abolish the death penalty. It also examines international trends to abolish the death penalty and proposes steps to ending the death penalty in countries that still assert it